Development and Application of Evaluation Procedure for Performance Testing of Vacuum Suction Pad in Automatic Mooring System in a Lab Test - Jeongnam Kim; Jaehyeon An; Youngki Kim; Youhee Cho (Journal of Marine Science and Engineering)
The fourth Industrial Revolution is driving the maritime and port logistics industry toward greater operational efficiency and reduced human intervention through automatic mooring systems. This study developed and applied a lab-based evaluation procedure to assess the performance and stability of vacuum suction pads in such systems. Test conditions were based on Cavotec’s specifications, with evaluation criteria tailored to the pads’ required performance. Relevant standards were reviewed to establish a vacuum pressure leakage criterion of 5% or less. Results showed that the pads maintained pressure reductions below this threshold, confirming their suitability for automatic mooring, though dynamic factors like heave and tides remain untested.